2022
DOI: 10.3389/fmed.2022.948299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modified techniques on outcomes of peroral endoscopic myotomy: A narrative review

Abstract: Peroral endoscopic myotomy (POEM) is an established frontline treatment modality for achalasia cardia. Since its initial description, several modifications have been proposed to the technique of POEM. Broadly speaking, these modifications follow the basic principles of submucosal endoscopy, but incorporate variations in the POEM technique, including the difference in the orientation of myotomy (anterior or posterior), length of myotomy (short or long), and thickness of myotomy (selective circular or full thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Adverse events occurred in a total of 26 cases (24.1%), half of which resulted from use of the anterior approach, 13/26 cases (50.0%) and the majority of these (10) occurred in the first 16 cases. A randomized pilot study and a narrative review supported the correlation between anterior myotomy and increased risk of mucosal injuries due to its need for greater scope tip angulation 23,24 , but the majority of findings of randomized clinical trials and systematic reviews have reported comparable outcomes for the two approaches. [25][26][27] In our study, the significant complications from anterior approach might be from early period of learning curve.…”
Section: Discussionmentioning
confidence: 94%
“…Adverse events occurred in a total of 26 cases (24.1%), half of which resulted from use of the anterior approach, 13/26 cases (50.0%) and the majority of these (10) occurred in the first 16 cases. A randomized pilot study and a narrative review supported the correlation between anterior myotomy and increased risk of mucosal injuries due to its need for greater scope tip angulation 23,24 , but the majority of findings of randomized clinical trials and systematic reviews have reported comparable outcomes for the two approaches. [25][26][27] In our study, the significant complications from anterior approach might be from early period of learning curve.…”
Section: Discussionmentioning
confidence: 94%
“…Some procedures such as POEM in achalasia and other EMD are in the first line of treatment for these pathologies and will probably appear as the treatment of choice in the updates to the main clinical guidelines. In achalasia, most of the technical and management aspects are clearly defined, although there are still areas for improvement (51). However, in other pathologies, the possibility of treatment by submucosal endoscopy needs to be defined both at a technical level and positioned in the therapeutic algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Later, most groups have shifted to the posterior orientation due to shorter and easier procedures with less inadvertent mucosotomy rate and same clinical success and reflux rate (47-49). Theoretically, any orientation could be performed (50), in fact, a second tunnel with a different orientation is an alternative in patients with submucosal fibrosis found in the initial tunnel (51). Full-thickness myotomy reduces the procedure duration without impairing clinical success nor increasing reflux (52).…”
Section: Poem Proceduresmentioning
confidence: 99%
“…Regarding the depth of myotomy, although full-thickness myotomy was initially believed to have a major positive impact on clinical success, both limited to the inner circular layer and full-thickness have shown similar efficacy and safety [11][12][13]. The latter is preferred at our institution due to its speed.…”
Section: Techniquementioning
confidence: 99%